A lipemia-independent NanoDrop®-based score to identify hemolysis in plasma and serum samples. (May 2014) - Appierto, Valentina; Callari, Maurizio; Cavadini, Elena; Morelli, Daniele; Daidone, Maria Grazia; Tiberio, Paola
Background: The identification and management of hemolyzed samples are crucial issues in the development of new blood-based biomarkers.Results: Using experiments of controlled hemolysis and lipemia and two plasma series from cancer patients, we developed and validated a lipemia-independent hemolysis score (HS). HS resulted strictly associated with the amount of lysed erythrocytes and with serum index measurement (reference method), highly reproducible, and able to identify as hemolyzed plasma/serum samples containing ≥6.1 mg/dl of free hemoglobin.Conclusion: We developed a simple, robust, sensitive, cost-effective, spectrophotometrically-based system to identify hemolyzed plasma/serum specimens. The procedure requires only 2 μl of sample, thus representing a useful tool for research studies and an essential pre-analytical quality control for an optimal biobanking of liquid biopsies.